BURST CAPACITY OF REINFORCED THERMOPLASTIC PIPE (RTP) UNDER IMPACT OF LATERAL LOAD - ABU BAKAR, MOHD AZIZUL (2021)
Reinforced Thermoplastic Pipe (RTP) is a type of spoolable composite pipe designed with complex multilayer properties